Evaluation of an intervention to promote minimally invasive dentistry (MID) in an Australian community dental agency—A pilot study. Issue 4 (2nd June 2021) - Nguyen, Tan Minh; Tonmukayakul, Utsana; Calache, Hanny
Abstract: Objectives: To evaluate the impact of an intervention consisting of a 1‐day continuing professional development (CPD) education programme on the International Caries Classification and Management System (ICCMS ™ ), and monthly performance feedback, and to promote minimally invasive dentistry (MID) for children aged under 12 years in an Australian community dental agency. The a priori hypotheses assumed the intervention would increase preventive services, and treatment demand was met. Methods: A quasi non‐randomized controlled trial with convenience sampling method was adopted. Fourteen dental practitioners received the intervention. The prevalence of dental caries and gingivitis in Australian children was used to determine the treatment demand and used as the performance benchmark. Ten types of preventive and non‐preventive dental services were examined. A Difference‐in‐Differences (DiD) of 12‐month pre‐ (baseline) and post‐intervention analysis was performed. Results: The intervention group demonstrated increases in topical fluoride application and dietary analysis and advice services. The standard care group had increases in oral prophylaxis or scale and clean, topical fluoride application and oral hygiene instructions ( p ‐value <0.05). The DiD analysis confirmed the above findings in the intervention group, while other preventive services declined. In the intervention group, the performance benchmark for oral prophylaxis or scale and clean and oral hygiene instructions was met at baseline and post‐intervention. Conclusions: Only a few preventive services had already met the performance benchmark. The intervention was associated with varied changes to preventive and non‐preventive dental services. More robust study design addressing the study limitations and validating the performance benchmark is required.